Disproportionate adverse event signals of selumetinib in neurofibromatosis type I: insights from FAERS - Li, Lin (Frontiers in pharmacology, 2025)
Neurofibromatosis type 1 (NF1) is a rare neurogenetic disorder with limited treatment options. Selumetinib, a MEK1/2 inhibitor, has emerged as a promising therapy for inoperable NF1-related plexiform neurofibromas. Our retrospective pharmacovigilance study utilized the FDA Adverse Event Reporting System (FAERS) to comprehensively evaluate Selumetinib's safety profile in real-world settings. Data from the third quarter of 2020 to the fourth quarter of 2023 were analyzed, identifying 498 adverse event reports with Selumetinib as the primary suspect drug. Statistical analysis revealed disproportionate signals for skin and subcutaneous tissue disorders, eye disorders, and various congenital, familial, and genetic disorders. The most common adverse events were elevated blood creatine phosphokinase, rash, and acneiform dermatitis. Notably, several adverse events, including rhabdomyolysis, were identified but not listed on the Selumetinib product label, based on a comparison with the FDA drug labeling. The study underscores the importance of early detection and management of adverse reactions associated with Selumetinib, particularly within the initial month of treatment. These findings provide valuable insights for clinicians and regulators to ensure the safe and effective use of Selumetinib in NF1 patients.